Synthesis and Characterization of Novel Magnetic Nanoparticles Supported Imidazole Ion as an Efficient Catalytic System for the Three-Component Reaction of Arylaldehydes, Malononitrile and α-hydroxy or α-Amino Active Methylene Compounds - Zahedifar, Mahboobeh; Mohammadi, Pourya; Sheibani, Hassan (Letters in Organic Chemistry, 2017)
Background: Recently, pyrimidine and chromene derivatives have concerned increasing attention because of the wide range of biological activities. Considering the prominence of pyrimidine and chromene derivatives, several procedures have been reported for the synthesis of these compounds. Herein, new magnetic nanoparticles supported ionic liquid has been evaluated for the synthesis of pyrimidine and chromene derivatives. Methods: In this method, pyrimidine and chromene compounds were synthesized by the multicomponent reaction of aromatic aldehydes, malononitrile, and active methylene compounds in the presence of the new magnetic nanoparticles supported ionic liquid. The new nanocatalyst was characterized by using TEM, VSM, XRD and IR spectrum. Results: The remarkable advantages of this new procedure involve high yields, short experimental time, low cast and easy preparation of the catalyst and no need of any workup and purification. Magnetic properties of the catalyst led to the easy separation from the reaction mixture by using an external magnet. The catalyst can be reused several times in the desired reaction without significant decrease of its activity. Conclusion: An efficient and green method for the synthesis of chromene and pyrimidine compounds in the presence of magnetic nanoparticles supported ionic liquid have been developed. Thermal stability, low cost and easy synthesis of the catalyst, high yields, easy separation and purification of the product, short experimental time and using a green solvent such as water provided a useful and alternative method for such reactions.
Keywords: magnetic nanocatalyst